2011
DOI: 10.1161/circgenetics.110.959205
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Significance and Replication of the Chromosome 12p11.22 Locus Near the PTHLH Gene for Peripartum Cardiomyopathy

Abstract: Background— Peripartum (PP) cardiomyopathy (CM) is a rare condition of unknown etiology that occurs in late pregnancy or early postpartum. Initial evidence suggests that genetic factors may influence PPCM. This study evaluated and replicated genome-wide association of single nucleotide polymorphisms with PPCM. Methods and Results— Genome-wide single nucleotide polymorphisms in women with verified PPCM diagnosis (n=41) were compared separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 35 publications
0
38
0
Order By: Relevance
“…Recurrence is common in subsequent pregnancy [4], and a genetic basis for the disease has been posited [5,6] and so has implications for family planning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recurrence is common in subsequent pregnancy [4], and a genetic basis for the disease has been posited [5,6] and so has implications for family planning.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to show some concordance in families, though this may simply be a first manifestation of familial dilated cardiomyopathy [5]. A genome-wide study has shown a strong association between a gene on chromosome 12 and PPCM [6].…”
Section: As a Geneticmentioning
confidence: 99%
“…7 There appears to be an association with the parathyroid hormone-like hormone ( PTHLH ) gene, which modulates vascular homeostasis via calcium channel agonisation. 8 Moreover, the TTN gene, which encodes the sarcomeric protein titin, has also been implicated in pathogenesis. 9 A novel hypothesis relates to excess prolactin production, which is associated with enhanced intravascular volumes, suppressed response to angiotensin and increased circulating erythropoietin levels.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Familial occurrence of PPCMP has been described and genetic association has been shown in mice and humans. 63,64 Recently, a large study on 172 PPCMP patients, showed a prevalence of truncating variants (especially in the Titin gene) similar to DCM patients, suggesting that these variants may predispose to the condition. 65 Myocarditis appears to be the main pathophysiological mechanism in PPCMP.…”
Section: Peripartum Cardiomyopathymentioning
confidence: 99%